PENGETAHUAN MODERASI BERAGAMA GURU MADRASAH ALIYAH NEGERI BANDA ACEH DAN ACEH BESAR - Rafidhah Hanum; Lina Rahmalia (Universitas Islam Negeri (UIN) Sumatera Utara, 2024)
The problem in this study is that the dynamics of intolerance are still very high in Indonesia. And educational institutions are the hope for the nation's people to instill religious moderation. The purpose of this study was to obtain information on the knowledge of Madrasah Aliyah teachers in Banda Aceh and Aceh Besar about religious moderation and also to find out the implementation of religious moderation in the teaching and learning process and what are the values of religious moderation built by teachers at MAN Banda Aceh and Aceh Besar. The researcher used a qualitative approach in order to describe the teacher's knowledge of religious moderation. The results of this study indicate that the values of religious moderation built by teachers at MAN Kota Banda Aceh and Aceh Besar are as follows: a) fair (Adl) students are free to make friends and are given full opportunity to play together, b) balanced (Tawazun) students do not offend each other's different backgrounds, c) simple (I'tidal) students are equipped with religious knowledge so that they become provisions at the next level so that they are not easily carried away by excessive currents in religion, d) unity and brotherhood (Ittihad wa Ukhuah) students care about each other